Experiencing racism within medical school curriculum: 2020 ICCH student symposium. Issue 7 (July 2022) - Hariharan, Bhairavi; Quarshie, Louisa Sowah; Amdahl, Christoffer; Winterburn, Sandra; Offiah, Gozie
Highlights: Racism in covert and institutional forms influences medical students experiences. Incorporation of anti-racism teaching into the medical curriculum is essential. Cultural competence training is important to reduce barriers to patient care. Anti-racism teaching should be included early and spiralled in the curriculum. Students' experiences provide thoughtful recommendations for educators. Abstract: Objective: To explore student experiences relating to racism, microaggressions and implicit bias within healthcare communication and medical education in the wake of the Black Lives Matter movement Methods: Students and faculty from different racial/ethnic backgrounds, medical schools, countries, and levels of training shared their perspectives with a multi-disciplinary, international audience at the 2020 International Conference on Communication in Healthcare (ICCH). Results: We highlight experiences shared at the symposium and demonstrate how the student voice can help shape the medical school curriculum. 3 main themes are discussed: 1) Institutional bias and racism, 2) Racial discrimination during medical training and 3) Recommendations for curricula change. Conclusion: Racism influences many aspects of student experiences and often appears in covert and institutional forms. These shared experiences reflect a common problem faced by ethnic minority medical students. Practice implications: Student experiences provide thoughtful recommendations for educators regarding incorporating anti-racism teaching into their curricula. It is essential that this teaching is collaborative, non-tokenistic and implemented early in the syllabus. It is beneficial for educators to build on the various existing approaches demonstrated by other institutions.